Optimizing oil quantity and quality of camelina (Camelina sativa L.) with integrative application of chemical, nano and bio-fertilizers under supplementary irrigation and rainfed condition - Mohammad Haghaninia; Abdollah Javanmard; Danial Kahrizi; Mir Babak Bahadori; Mostafa Amani Machiani (Plant Stress, 2024)
The cultivation of camelina (Camelina sativa L. Crantz) is increasing day by day owing to its high levels of oil content and potential source of α-linolenic acid, a precursor for omega-3 fatty acid. However, cultivation under drought stress, (e.g., under rainfed conditions) has a negative impact on the productivity and oil quality of oil-seed crops, while supplementary irrigation in sensitive growth periods of plants improves plant performance by increasing nutrient absorption rate. This study aimed to examine the effects of different sources of fertilizers on nutrient content, agronomic traits, quantity, and quality of camelina oil under rainfed and irrigated conditions. Treatments included i) no fertilization (control), ii) complete chemical fertilizer (CF), iii) bio-fertilizer (BF), iv) chitosan nanoparticles (CS), v) 50 % CF + BF, vi) 50 % CF + CS, vii) BF + CS, and viii) 50 % CF + BF + CS under rainfed and irrigated conditions (supplementary irrigation). The maximum concentrations of N, P, and K were obtained under supplementary irrigation with application of 50 % CF + BF + CS. Likewise, the maximum biological yield, seed yield, and oil yield were obtained under supplementary irrigation with application of BF + CS + 50 % CF. In addition, the maximum activity of glutathione peroxidase (GPX), glutathione reductase (GR), superoxide dismutase (SOD), polyphenol oxidase (PPO), and phenylalanine ammonia lyase (PAL) were recorded in rainfed conditions and with the integrative application of 50 % CF + BF + CS. Furthermore, the highest content of anthocyanin and ascorbic acid were observed in rainfed conditions treated with BF + CS + 50 % CF. The main compounds of camelina oil were saturated fatty acids including palmitic and stearic acids as well as unsaturated fatty acids containing oleic, linoleic, linolenic, and eicosenoic acid, respectively. Supplementary irrigation along with the integrative application of BF + CS and 50 % CF + BF + CS improved the oil quality of camelina through increasing the unsaturated fatty acids such as oleic, linoleic, linolenic, eicosenoic, and erucic acids. Overall, supplementary irrigation with the integrative application of fertilizers, especially 50 % CF + BF + CS, could be a sustainable strategy for improving the content and quality of camelina oil in rainfed conditions.